Penggunaan Sistem Klasifikasi di Perpustakaan Daerah provinsi Lampung Sebagai Bentuk Peningkatan Pengelolaan Perpustakaan - Kesuma, Mezan el-Khaeri; Yunita, Irva; Putri, Mutiara Cahyani (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
Introduction. The material discussed in this journal is to explain and describe in detail the use of the classification system at the Regional Library of Lampung Province, what system is used, how it is used. Data Collection Methods. The method used in this journal research is interview research and documentation study. The author also uses qualitative methods and literature studies. Data Analysis. Analysis of the data using data reduction, data presentation, and make conclusions about the Regional Library of Lampung Province. Results and Discussion. The results of this study are that the Lampung Provincial Library Service uses 2 classification systems, namely a manual system and also a digital system with the E-DDC application. The librarian at the Lampung Provincial Library Service uses E-DDC edition 23, although using two classification systems, the librarian at the Lampung Provincial Library Service still uses a manual system more often because if you use a digital system with the E-DDC application the librarian sometimes has problems when use it, however, the use of the E-DDC application is still being used today. Conclusion. The use of the classification system in the Regional Library of Lampung Province uses two classification systems, namely the manual system and the E-DDC (Electronic-Dewey Decimal Classification) application. The manual system is still often used by librarians of the Lampung Province Regional Library, even so the E-DDC application is still used but rarely because sometimes it gets obstacles when you want to use it.